Occupational segregation, gender essentialism and male primacy as major barriers to equity in HIV/AIDS caregiving: Findings from Lesotho - Makoae Lucia; Fogarty Linda; Newman Constance J; Reavely Erik (BMC, 2011)
Abstract Background Gender segregation of occupations, which typically assigns caring/nurturing jobs to women and technical/managerial jobs to men, has been recognized as a major source of inequality worldwide with implications for the development of robust health workforces. In sub-Saharan Africa, gender inequalities are particularly acute in HIV/AIDS caregiving (90% of which is provided in the home), where women and girls make up the informal (and mostly unpaid) workforce. Men's and boy's entry into HIV/AIDS caregiving in greater numbers would both increase the equity and sustainability of national and community-level HIV/AIDS caregiving and mitigate health workforce shortages, but notions of gender essentialism and male primacy make this far from inevitable. In 2008 the Capacity Project partnered with the Lesotho Ministry of Health and Social Welfare in a study of the gender dynamics of HIV/AIDS caregiving in three districts of Lesotho to account for men's absence in HIV/AIDS caregiving and investigate ways in which they might be recruited into the community and home-based care (CHBC) workforce. Methods The study used qualitative methods, including 25 key informant interviews with village chiefs, nurse clinicians, and hospital administrators and 31 focus group discussions with community health workers, community members, ex-miners, and HIV-positive men and women. Results Study participants uniformly perceived a need to increase the number of CHBC providers to deal with the heavy workload from increasing numbers of patients and insufficient new entries. HIV/AIDS caregiving is a gender-segregated job, at the core of which lie stereotypes and beliefs about the appropriate work of men and women. This results in an inequitable, unsustainable burden on women and girls. Strategies are analyzed for their potential effectiveness in increasing equity in caregiving. Conclusions HIV/AIDS and human resources stakeholders must address occupational segregation and the underlying gender essentialism and male primacy if there is to be more equitable sharing of the HIV/AIDS caregiving burden and any long-term solution to health worker shortages. Policymakers, activists and programmers must redress the persistent disadvantages faced by the mostly female caregiving workforce and the gendered economic, psychological, and social impacts entailed in HIV/AIDS caregiving. Research on gender desegregation of HIV/AIDS caregiving is needed.